2022
DOI: 10.1186/s13287-021-02689-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell-based therapy for cartilage regeneration in knee osteoarthritis

Abstract: Osteoarthritis, as a degenerative disease, is a common problem and results in high socioeconomic costs and rates of disability. The most commonly affected joint is the knee and characterized by progressive destruction of articular cartilage, loss of extracellular matrix, and progressive inflammation. Mesenchymal stromal cell (MSC)-based therapy has been explored as a new regenerative treatment for knee osteoarthritis in recent years. However, the detailed functions of MSC-based therapy and related mechanism, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 178 publications
(238 reference statements)
1
46
0
Order By: Relevance
“…The formation of cartilage may be due to spontaneous cell migration in the joint environment, and we speculate that this fraction of endogenous cells is derived from the stem or progenitor cells from the bone marrow, the synovium, the adipose (fat pad adjacent to the synovium and bone marrow), and perhaps vasculature, which have the better chondrogenic potential [ 2 ]. In the case of cartilage repair, stem/progenitor cells may initiate targeted repair systems that promote trophic effects by releasing synthetic, proliferative, and regenerative factors directly into cartilage damage, and create a regenerative environment by releasing chemokines [ 46 ]. The evaluation of repairing articular cartilage defects in hybrid pig models confirmed that the ACM-based scaffold can repair articular cartilage defects within 6 ​mm in diameter, but the effect is not satisfactory for a larger range of articular cartilage defects.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of cartilage may be due to spontaneous cell migration in the joint environment, and we speculate that this fraction of endogenous cells is derived from the stem or progenitor cells from the bone marrow, the synovium, the adipose (fat pad adjacent to the synovium and bone marrow), and perhaps vasculature, which have the better chondrogenic potential [ 2 ]. In the case of cartilage repair, stem/progenitor cells may initiate targeted repair systems that promote trophic effects by releasing synthetic, proliferative, and regenerative factors directly into cartilage damage, and create a regenerative environment by releasing chemokines [ 46 ]. The evaluation of repairing articular cartilage defects in hybrid pig models confirmed that the ACM-based scaffold can repair articular cartilage defects within 6 ​mm in diameter, but the effect is not satisfactory for a larger range of articular cartilage defects.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic regenerative properties of MSCs may allow these cells to repair cartilage, as well as dampen inflammation in the joint due to their recognised local immunosuppressant effects ( Gao et al, 2016 ; Wang et al, 2018 ; Harrell et al, 2019 ; Song et al, 2020 ; Zhao et al, 2020 ; Hwang et al, 2021 ; Zhu et al, 2021 ; Xiang et al, 2022 ). However, MSC transplantation attempts in OA clinical trials have thus far produced limited evidence of cartilage regeneration, despite reported improvements in pain and physical function ( Iijima et al, 2018 ; Wang et al, 2020 ; Zhu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that endogenous cartilage regeneration is limited ( Heng et al, 2004 ; Kock et al, 2012 ), novel approaches aiming to restore joint tissue through the use of mesenchymal stem cells (MSCs) are emerging. These progenitors can differentiate into osteoblasts and chondrocytes, and therefore have the potential to promote the regeneration of damaged cartilage ( Hwang et al, 2021 ; Zhu et al, 2021 ; Xiang et al, 2022 ). Pre-clinical studies have revealed that while endogenous populations of synovial MSCs can contribute to cartilage repair following chondrogenesis ( Harrell et al, 2019 ), the exogenous delivery of MSCs may result in a reduction in cartilage degradation and pain ( Chapman et al, 2017 ; Harrell et al, 2019 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cell therapy is based mainly on the use of stem cells, as they present critical properties for tissue regeneration, such as self-renewal and differentiation potential for several cell lineages. Strategies for cartilage regeneration using induced pluripotent stem cells (iPSCs) or adult stem cells, primarily mesenchymal stem cells (MSCs), are described elsewhere and thoroughly reviewed here [ 26 , 27 , 28 ]. In the last decade, several works have associated the beneficial aspects of stem cell therapies with the factors secreted by them, which act via paracrine signaling and influence the cellular microenvironment [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%